2005
DOI: 10.1073/pnas.0407983102
|View full text |Cite
|
Sign up to set email alerts
|

Core 3 synthase is down-regulated in colon carcinoma and profoundly suppresses the metastatic potential of carcinoma cells

Abstract: The core 3 structure of the O-glycan, GlcNAc␤1-3GalNAc␣1-Ser͞ Thr, an important precursor in the biosynthesis of mucin-type glycoproteins, is synthesized by ␤1,3-N-acetylglucosaminyltransferase 6 (␤3Gn-T6; core 3 synthase). We generated an anti-␤3Gn-T6 mAb (G8-144 mAb) and performed immunohistochemical analyses. In normal stomach and colon, ␤3Gn-T6 was strongly expressed in the Golgi region of epithelia. In contrast, its expression was markedly down-regulated in gastric and colorectal carcinomas. Tissue specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
132
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 40 publications
4
132
1
Order By: Relevance
“…By stable transfection of HCT116 cells, we found that C2GnT-M also decreased the core 1 structure, suggesting that this could be due to the processing of the core 1 structure (T antigen) to core 2 through C2GnT activity of C2GnT-M. Core 3 synthase was found to be significantly downregulated in colon cancer (Iwai et al, 2005). In addition, we could not detect I antigen expression on mock and C2GnT-M transfectants of HCT116.…”
Section: C2gnt-m In Colorectal Cancermentioning
confidence: 71%
“…By stable transfection of HCT116 cells, we found that C2GnT-M also decreased the core 1 structure, suggesting that this could be due to the processing of the core 1 structure (T antigen) to core 2 through C2GnT activity of C2GnT-M. Core 3 synthase was found to be significantly downregulated in colon cancer (Iwai et al, 2005). In addition, we could not detect I antigen expression on mock and C2GnT-M transfectants of HCT116.…”
Section: C2gnt-m In Colorectal Cancermentioning
confidence: 71%
“…Recently, we found that C2GnT-M overexpression decreases colon cancer cell growth and tyrosine phosphorylation of paxillin, which is an important downstream signaling molecule of integrins (12). In addition, h3Gn-T6 was found to decrease core 1 structure and suppress metastatic potential of colon carcinoma cells through an unclear mechanism (13). These studies suggest that glycosyltransferases can regulate cancer cell behavior through alterations of integrin glycosylation or through other mechanisms which remain to be identified.…”
Section: Introductionmentioning
confidence: 91%
“…Expression of core3 synthase in a human fibrosarcoma cell line also resulted in decreased lung tumor foci formation compared with mock-transfected cells (16). However, these studies did not address the mechanisms regarding how core3 synthase expression results in decreased tumor formation and decreased tumor metastasis.…”
Section: Core3 Synthase-expressing Prostate Cancer Cell Lines Exhibitmentioning
confidence: 99%